DESAIN SISTEM INFORMASI KEUANGAN PENDAPATAN UANG SEKOLAH PADA PERHIMPUNAN PENDIDIKAN (PERHIMPUNAN ABC) - Henry Novirga Tandyo (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2018)
Nonprofit organizations in the field of service generally focus on the services they provide. This resulted in a lack of attention to the company's internal controls, one of which is the financial field. This study aims to design standard operating procedures of school tuition income on educational foundations using the model of financial information systems. This research uses qualitative method with exploratory case study approach. In addition, researchers also participated directly in this research as a consultant. The results of this study indicate that workmanship in the field of finance has a problem related to the reliability of information displayed both in the form of financial statements and management reports. The absence of Standard Operating Procedure is a major cause of this problem. Standard Operating Procedures can be a problem solver in tracking any problems that result in the lack of financial reports and management reports on the Education Foundation. Keywords: Financial Information System, Non-profit Organization, Revenue, Internal Control, Standard Operating Procedure.